Retentive ocular prosthesis restores post evisceration patients’ physical and psychological - Steven Syahputra; Ariyani Dallmer; Putri Welda Utami Ritonga; Haslinda Z. Tamin (Indonesia Prosthodontic Association, 2022)
Loss of eye does not only affect facial esthetics but also psychological health of the patient and leads to social disa-bility. A custom-made ocular prosthesis is a good alternative to promote physical, psychological and esthetically plea-sing appearance that can improve social acceptance of the patient. A 5-years-old female patient and 18-years old male patient were reported to Dental Hospital USU with the chief complaint of loss of an eye, making them often in-sulted by schoolmates, while the male patient lost confidence on socializing around. In these cases, ocular prosthe-ses with modification of custom tray was made by using a putty index obtained from wax pattern to produce a better fitting ocular prosthesis so it expected to be retentive as to produce comfort and increase patient confidence. Con-tact between ocular prosthesis and tissue bed is necessary to evenly distribute the pressure obtained with proper im-pression technique. This technique ensures a good fit of the custom tray thereby produce accurate adaptation to the tissue surface can increase the movement of the prosthesis and provide a good natural esthetic outcome. Post evi-sceration patients need psychological support to restore confidence and self-esteem in today's cosmetics challenging world. For these cases, patients’ self-confidence was restored and socializing as before without any embarrassment.